Pengaruh Pendidikan Kesehatan Media Video Animasi Menstrual Hygiene Management Terhadap Pengetahuan dan Sikap Remaja Putri - Nurhidayah, Nurhidayah; Herlina, Herlina; Guna, Stephanie Dwi (Innovative: Journal Of Social Science Research, 2024)
Menstrual Hygiene Management is the practice of maintaining the cleanliness and health of the reproductive organs during the menstrual period. This action involves the duration of changing pads, the duration of changing underwear per day, and the correct way to clean the genital area. The research design uses a quasi-experimental one group pre-test post-test. This research was conducted from September 25 to October 24, 2024, at SMPN 9 Pekanbaru with a sample size of 34 respondents selected based on inclusion criteria using purposive sampling technique. The analysis were univariate and bivariate analysis with the Wilcoxon test. This research uses a questionnaire on knowledge and attitudes about menstrual hygiene management and an animated video media containing material on menstrual hygiene management. Most of the respondents were 13 years old (41.2%), and the age of menarche for the respondents was 11 years old (52.9%).there was an increase in the knowledge of adolescent girls in good knowledge (100%) after being provided with health education through animated video media about menstrual hygiene management. In terms of attitude, there is an increase in positive attitude with a mean score of 56.91. Statistical tests yielded a p-value (0.000) < α (0.05), indicating an increase in knowledge about menstrual hygiene management. For the attitude variable, a p-value (0.000) < α (0.05) was obtained, indicating a change in attitude towards menstrual hygiene management. There is an Influence of Health Education through Animated Video Media on Menstrual Hygiene Management on the Knowledge and Attitudes of Adolescent Girls.